Pyrolysis Reaction Kinetics of Styrofoam Plastic Waste - Kauwo, Feybi A. G.; Anom, I Dewa K.; Lombok, John Z. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2021)
Pyrolysis at the temperature range of 170 Â°C-237 Â°C against polystyrene (Styrofoam) type plastic waste is carried out without a catalyst and added a catalyst. The purpose of this research was to study the reaction kinetics of Styrofoam pyrolysis to liquid smoke products. Pyrolysis using a series of tools made of glass to observe the processes that occur in the reactor. The results showed that Styrofoam pyrolysis for liquid smoke products without catalyst and added catalyst took place in the first-order reaction. The kinetics of the pyrolysis reaction without a catalyst to observe the formation of liquid smoke products obtained by the equation of the reaction constant following the Arrhenius equation k = Ae2111.4 / T, with an activation energy value (Ea) of 17.554 x 103 kJ/mol and pyrolysis using a catalyst obtained k = Ae10330/T, with an activation energy value (Ea) of 85.883x103 kJ/mol. Using catalysts during pyrolysis will reduce the temperature so that the reaction will be slow.